Rural transformation, income growth, and poverty reduction by region in China in the past four decades - Peng-fei SHI; Ji-kun HUANG (Journal of Integrative Agriculture, 2023)
China has experienced rapid rural transformation in the past four decades. Accompanying the rapid transformation is a significant rise in rural household income and a substantial fall in rural poverty. This paper examines the evolutions of and the relationships between rural transformation (high-value agriculture and rural non-farm employment) and its outcomes (per capita rural income and rural poverty incidence) using provincial-level data. The results show that 31 provinces/autonomous regions/municipalities have undergone significant rural transformation, but the level and speed of rural transformation differed considerably. Moreover, an increased level of rural transformation is often associated with higher per capita rural income and reduced rural poverty incidence. Notably, a category of provincial rural transformation based on high-value agriculture and rural non-farm employment is also analyzed. We further discuss the likely impacts of institutions, policies, and investments (IPIs) on rural transformation and conclude with policy implications.